Epidendrum edquenii (Laeliinae), a new species from a montane wet forest of the Private Conservation Area La Pampa Del Burro, Amazonas, Peru - Arista Bustamante, Jessy Patricia; Hágsater Gartenberg Eric 1945-; Santiago Ayala, Elizabeth 1973-; Pariente Mondragón, Elí (2023)
A new species, Epidendrum edquenii, is described and illustrated from the Private Conservation Area La Pampa del Burro, department of Amazonas, northeastern Peru. It belongs to the informal Takulumena group, characterized by Vanda-like monopodial stems with basal or lateral, successive inflorescences. The new species is distinguished by its non-pubescent, red flowers with green dorsal surface, margins, and apices of the sepals and petals, yellow-green base of column and disc of lip, acuminate sepals 9.5-10.7 mm long, narrowly ovate petals with the margin densely and shortly ciliate, and widely triangular lip, 6.0 × 9.5 mm, with the margin scarcely papillose. A list and an identification key for the previously known species of the Takulumena group are provided. Furthermore, the new name Epidendrum vulcanitungurahuae is proposed to replace the illegitimate combination Epidendrum tungurahuae, predated by E. tunguraguae.
Se describe e ilustra una nueva especie, Epidendrum edquenii, del Área de Conservación Privada La Pampa del Burro, departamento de Amazonas, noreste de Perú. Pertenece al grupo informal Takulumena, que se caracteriza por sus plantas monopodiales con tallos similares a Vanda e inflorescencias sucesivas, basales o late-rales. La nueva especie se distingue por las flores rojas, no pubescentes, con superficie dorsal, márgenes y apices de sépalos y pétalos verdes, base de la columna y disco del labelo amarillo-verde, sépalos acuminados 9.5-10.7 mm de largo, pétalos angostamente ovados con el margen densa y cortamente ciliado y el labelo, ampliamente triangular, 6.0 × 9.5 mm, con el margen escasamente papiloso. Se presenta una lista y una clave para la identifi-cación de las especies conocidas del grupo Takulumena. Se propone el nuevo nombre Epidendrum vulcanitun-gurahuae para reemplazar la combinación ilegítima Epidendrum tungurahuae, antecedida por E. tunguraguae.
Keywords: LAELIINAE -- IDENTIFICACION -- AMAZONAS (PERÚ); LAELIINAE -- CLASIFICACIÓN -- AMAZONAS (PERÚ); ESPECIES -- IDENTIFICACION